Implementing Underground Water Storage Tank to Stabilize Intermittent Water Supply in Jakarta, Indonesia - Nicco Plamonia; Rizky Pratama Adhi; Merri Jayanti; Muhammad Komarudin; Budi Kurniawan; Syaefudin Syaefudin; Ahmad Pratama Putra; Luky Pradita; Raden Arif Suryanegara; Haerul Hidayaturrahman; Ikhsan Budi Wahyono; Shafira Rahmadilla Hape (Journal of Regional and City Planning, 2026)
This study addresses the issue of intermittent water supply in Jakarta, focusing on the use of underground water storage tanks (UWSTs) to stabilize water availability in three commercial buildings. Surveys showed that the average pressure from drinking water utilities over five consecutive days was only 4 m head—considered critically low. The research proposes installing UWSTs to store water during off-peak hours for redistribution during peak demand or supply outages. The study also analyzed the influence of commuter and resident water-use patterns, with an estimated tank capacity of 25.69 m³ per site to accommodate varying demand. Field data processing and simulations demonstrated that UWSTs can markedly improve supply consistency, particularly during peak hours. Optimizing the tank design within the space constraints in the buildings proved effective in balancing storage capacity and structural integrity. The integration of UWSTs with pressure-management strategies offers a practical and resilience-based approach to Jakarta’s urban water-supply challenges. Residential and office-sector consumption data were specifically integrated into a composite daily pattern to characterize urban peak-demand behavior in Jakarta. The solution proposed in this study is considered sustainable because it utilizes the existing water supply without increasing extraction, while improving temporal distribution efficiency during low-pressure periods.